Demographic changes and the implicit tax rate in a pay-as-you-go pension system - Mathias Kifmann; Dirk Schindler (Universität Konstanz, Fachbereich Wirtschaftswissenschaften, 2000)
We analyze the effects of a permanent increase in life expectancy and of a permanent decline in the rate of population growth on intergenerational redistribution in a pay-as-you-go pension system with a constant contribution or constant replacement rate. We show that under these policies both demographic changes increase the implicit tax rate of later-born generations to the pension system. In addition, we characterize policies which smooth the implicit tax rate. To reach this objective, generation-specific contribution or replacement rates are necessary. Partial funding of the pension system is indispensable if the rate of population growth falls. If life expectancy increases, the contribution rate fluctuates and may not converge to a new steady state value unless funded elements are introduced.
Keywords: H55; J18; 330; Pay-as-You-Go; implicit tax rate; life expectancy; population growth